Peran Lembaga Pemerintahan Dalam Mendukung Tugas dan Fungsi Baznas Bidang Pemberdayaan Zakat di Kota Bengkulu - Yusmita Yusmita (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
In Law no. 38 of 1999, the position of government and society is equal in the management of zakat, whereas, in Law no. 23 of 2011, the position of the government and BAZNAS is higher. On the other hand, ideally, government agencies in the city of Bengkulu should help and support the duties and functions of BAZNAS institutions in empowering zakat in the city of Bengkulu. This research is field research. The type of research approach is descriptive-qualitative, using interview data collection techniques and documentation from BAZNAS and regional government data. The results of this study indicate that, From the results of the analysis carried out, the researchers can conclude as follows: The role of government agencies in supporting the duties and functions of BAZNAS in Bengkulu City, the number of agency official data is 126, only 49 institutions that pay Makadari, around 39% have already pay zakat to BAZNAS Bengkulu Province, while 77 agency agencies or 61% have not paid zakat at BAZNAS Bengkulu Province, it can be concluded that the role of BAZNAS Bengkulu province has played a role but not optimally well, while the background factors for government agencies distribute zakat through BAZNAS includes: Implementing government regulations regarding zakat, carrying out circulars from superiors, socialization from BAZNAS, leadership orders while the background factors for government agencies not channeling zakat through BAZNAS are: There is a top circular regarding the prohibition of salary deductions, Lack of BAZNAS Socialization, Understanding and awareness lack of religion, lack of trust in BAZNAS institutions, procedural errors in appointing BAZNAS and UPZ officials. Dalam UU No. 38 tahun 1999 posisi pemerintah dan masyarakat sejajar dalam pengelolaan zakat, sedangkan dalam UU No. 23 tahun 2011 posisi pemerintah dan BAZNAS lebih tinggi, Di sisi lain, idealnya lembaga pemerintahan yang ada di kota Bengkulu seharusnya membantu dan mendukung tugas dan fungsi lembaga BAZNAS dalam pemberdayaan zakat di Kota Bengkulu. Penelitian ini merupakan penelitian lapangan (field research). Adapun jenis pendekatan penelitian ini adalah deskripitif-kualitatif, dengan teknik pengumpulan data wawancara dan dokumentasi dari data baznas dan pemerintahan daerah. Hasil penelitian ini menujukkan bahwa, dari hasil analisa yang dilakukan maka dapat peneliti simpulkan sebagai berikut: Peran lembaga pemerintah dalam mendukung tugas dan fungsi baznas di Kota Bengkulu jumlah data dinas instansi yang ada 126 hanya 49 lembaga yang mebayar makadari itu berkisar 39 % saja yang sudah membayar zakat ke BAZNAS Provinsi Bengkulu, sedangkan 77 lembaga dinas instansi atau 61 % belum membayar zakat di BAZNAS Provinsi Bengkulu, dapat disimpulkan bahwa peran lembaga BAZNAS provinsi Bengkulu sudah berperan tapi belum secara maksimal dengan baik, sedangkan faktor yang melatar belakangi lembaga pemerintah menyalurkan zakat melalui Baznas antara lain: melaksanakan aturan pemerintah tentang zakat, melaksanakan edaran atasan, adanya sosialisasi dari BAZNAS, Perintah pimpinan sedangkan faktor yang melatar belakangi lembaga pemerintah tidak menyalurkan zakat melalui BAZNAS yaitu: Adanya edaran atasa tentang larangan pemotongan gaji, Kurangya Sosialisasi BAZNAS, Pemahaman dan kesadaran keagamaan yang kurang, Kurangnya Kepercayaan kepada lembaga BAZNAS, Kesalahan prosedur pengangkatan pejabat BAZNAS dan UPZ.